Cervical proprioception and its relationship with neck pain intensity in subjects with cervical spondylosis - Reddy, Ravi Shankar; Tedla, Jaya Shanker; Dixit, Snehil; Abohashrh, Mohammed (BMC musculoskeletal disorders, 2019)
Background Cervical proprioception is critical in the maintenance of posture and movements, so its assessment in different cervical conditions has gained importance in recent clinical practice. Studies reporting this assessment in subjects with cervical spondylosis (CS) have not previously been investigated. The goals of the study are (1) comparison of joint position error (JPE) in subjects with CS to healthy control group. (2) Correlation of neck pain intensity to cervical proprioception in patients with CS. Methods In a Cross-sectional study, 132 subjects with CS and 132 healthy age-matched control subjects were evaluated for cervical JPE with the cervical range of motion device. The subjects were blindfolded and repositioned their heads to a target position, which was determined by the examiner previously and their repositioning accuracy (absolute error in degrees) was measured in the frontal (flexion and extension) and transverse planes (left rotation and right rotation). The CS subjects resting neck pain intensity was assessed using visual analog scale (VAS). Results CS subjects showed statistically significantly larger JPEs compared to healthy control subjects in all the directions tested (flexion - 95% CI = 2.38–3.55, p < 0.001, extension - 95% CI =3.26–4.33, p < 0.001, left rotation - 95% CI = 2.64 - 3.83, p < 0.001, right rotation − 95% CI = 3.77–4.76, p < 0.001). The mean JPE errors in the CS group ranged from 6.27° to 8.28° and in the control group ranged from 2.36° to 4.48°. Pearson’s correlation coefficient showed a significant and positive relationship between neck pain intensity and cervical proprioception ( p ≤ 0.001). Conclusions Proprioception is impaired in subjects with CS when compared to healthy control group. Higher pain intensity was associated with greater cervical JPE in patients with CS.